STRATEGI BADAN PENGAWAS PEMILIHAN UMUM (BAWASLU) ACEH TENGGARA DALAM MENINGKATKAN PARTISIPASI MASYARAKAT PADA PENGAWASAN PEMILU 2024Studi Kasus PSU (Pemungutan Suara Ulang) Desa Petanduk kecamatan Semadam dan Desa lawe Aunan kecamatan Ketambe - Mustapa Kamil Alga Beruh; Lusiana Lusiana (SUAN PUBLISHER, 2024)
Democracy in Indonesia is experiencing very rapid changes, namely the influence of increasingly modern information technology, Bawaslu as an important institution in monitoring and preventing election violations with the aim of producing good leaders in accordance with the choices of the Indonesian people. Bawaslu Southeast Aceh district has made efforts to optimize overall capabilities in making the 2024 elections a success. And social media is an important instrument in current developments, almost 65 percent of the people of Southeast Aceh District have used social media networks. Southeast Aceh Regency Bawaslu uses social media as a work tool to publish information and existing activities. Of course, Bawaslu cannot work alone without being actively supported by the community, but the participation of the people of Southeast Aceh Regency is still lacking in helping to make monitoring and preventing election violations a success. Through existing technological opportunities, namely work networks, the community is actively involved in monitoring and preventing election violations, therefore it is necessary to have social trust in Bawaslu and guarantee